A Multi-agent model for supporting exchange dynamics in social support networks during stress - Ab. Aziz, Azizi; Ahmad, Faudziah (Springer International Publishing AG, 2013)
Humans are social creatures, and when facing certain level of events, they to seek for support from others and vice versa.In this paper, a multi-agent model for simulating the dynamics of support provision and receipt interaction among different individuals is presented.Important concepts in social support network and stress buffering studies were used as the basis for model design and verification. Simulation experiments under several cases pointed out that the model is able to reproduce interaction among social support network members during stress.Mathematical analysis was conducted to determine possible equillibria of the model.The model was verified using an automated verification tool against generated traces.